Maleic, glycolic and acetoacetic acids-leaching for recovery of valuable metals from spent lithium-ion batteries: leaching parameters, thermodynamics and kinetics. Issue 9 (4th September 2019) - Liu, Borui; Huang, Qing; Su, Yuefeng; Sun, Liuye; Wu, Tong; Wang, Guange; Kelly, Ryan M.; Wu, Feng
Abstract : Environmentally friendly acid-leaching processes with three organic acids (maleic, glycolic and acetoacetic) were developed to recover valuable metals from the cathodic material of spent lithium-ion batteries (LiCoO2 ). The leaching efficiencies of Li and Co by the maleic acid were 99.58% and 98.77%, respectively. The leaching efficiencies of Li and Co by the glycolic acid were 98.54% and 97.83%, while those by the acetoacetic acid were 98.62% and 97.99%, respectively. The optimal acid concentration for the maleic acid-, glycolic acid- and acetoacetic acid-leaching processes were 1, 2 and 1.5 mol l –1, respectively, while their optimal H2 O2 concentrations were 1.5, 2 and 1.5 vol%, respectively. The optimal solid/liquid ratio, temperature and reaction time for the leaching process of the three organic acids was the same (10 g l −1, 70°C, 60 min). The thermodynamic formation energy of the leaching products and the Gibbs free energy of the leaching reactions were calculated, and the kinetic study showed that the leaching processes fit well with the shrinking-core model. Based on the comparison in the leaching parameters, the efficacy and availability of the three acids is as follows: maleic acid > acetoacetic acid > glycolic acid.